Investment Literacy and Business Decisions of Students in Public Universities in Bayelsa State - Festus Emeke OGWU (Journal of Accounting and Financial Management, 2026)
Abstract This research examined how investment literacy affects business decisions of students in public universities of Bayelsa State with special emphasis on the diversification literacy and risk awareness. The study used cross-sectional survey design with samples comprising of trainee accountants in Niger Delta University, Federal University Otuke and University of Africa, Toru-Orua. The total population of 1473 students were taken and Taro Yamane formula gave an estimate of 315 respondents which were proportionately distributed to the three universities according to Bowley statistics. The data were gathered with the help of a structured questionnaire measured on a five-point Likert scale and analysed with the aid of multiple linear regression in SPSS version 26. The retrieval rate of the questionnaire was 86 percent with 280 of the 315 copies being retrieved. The results showed that diversification literacy has a positive and significant contribution to business decisions which means that students who know how to allocate resources to different investment opportunities make more balanced and informed financial decisions. Likewise, it was observed that risk awareness has a positive and significant effect indicating that students that are able to identify, analyze as well as act on possible uncertainties in investment situations make effective decisions. The research concluded that investment literacy has a substantial effect on the business decisions of students in public university of Bayelsa State. It was recommended based on the findings that Universities should enhance diversification literacy by providing workshops and practical simulations to students, and professional unions and Student Union Governments should increase risk awareness by mentoring and workshops.